RETHINKING THE EPISTEMOLOGY OF ISLAMIC ECONOMY: ABBAS MIRAKHOR’S CONTRIBUTION TO THE CURRENT DEBATE - Khoiri, Imam (Universitas Islam Indonesia, 2019)
In the last three decades, Islamic economics and finance have experienced significant developments. At the same time, several problems arise, not only technical but also epistemological. On that basis, the author is interested in studying Abbas Mirakhor’s epistemological thought, in the hope of providing answers to these problems while providing direction for the next steps. As a qualitative study, the primary data source of this research is the work of Abbas Mirakhor. This study uses philosophical, sociological and historical approaches in addition to the literature review approach. The results of the study show that in the view of Abbas Mirakhor, the source of the formulation of the Islamic economic concept is the Qur’an, Sunnah, and Islamic jurisprudence. The reading of the Qur’an and Sunnah is done through the perspective of the NIE (New Institutional Economics). Through this approach, where Islam is placed as a rule-based system, the Islamic economic scaffolding formulation consists of rules about property, markets, distribution and redistribution, risk sharing, contracts, and trusts. Adherence to institutional scaffolding correlates with economic growth. This institutional scaffolding is supported by an incentive structure through the concept of barakah.